Metal levels in Trachurus trachurus and Cyprinus carpio in Turkey - Yaman, Mehmet; Bal, Tulin; Yaman, Ibrahim H. (Taylor & Francis Ltd, 2013)
Concentrations of five toxic metals were determined in two fish species from Turkish cities during 2010-2011. The obtained lead concentrations for all of the studied Trachurus trachurus (mean 777g kg(-1)) and Cyprinus carpio (mean 439g kg(-1)) samples were found to be higher than the maximum level (ML) of 300g kg(-1), while Cd concentrations in the same samples were lower than the ML. Mean chromium (501g kg(-1)), Ni (272g kg(-1)) and Cu (785g kg(-1)) concentrations in T. trachurus were significantly higher than in C. carpio (336g Cr kg(-1), 229g Ni kg(-1) and 394g Cu kg(-1)), similar to those of Pb and Cd. Measured Pb concentrations in T. trachurus tissues are significantly higher than the ML, while those of Cd in both T. trachurus and C. carpio species were lower than the ML values.
Keywords: lead; cadmium; copper; nickel; chromium; heavy metals; fish; atomic absorption; ICP-AES